GAYA KEPEMIMPINAN SITUASIONAL DI PERPUSTAKAAN JARINGAN DOKUMENTASI DAN INFORMASI HUKUM KABUPATEN SLEMAN - Shinta Nofita Sari; Fitri Kartika Sari (Jurnal Pustaka Ilmiah, 2020)
The research was conducted in the documentation and legal Information Library (JDIH) Sleman Regency, Yogyakarta. The purpose of this study is to be able to know how to apply situational leadership styles in the JDIH library. The method used in this research is a qualitative descriptive through the case study approach. The result of this research is the library JDIH Sleman Regency, Yogyakarta its leadership style belongs to the style of situational leadership because the leader has strict characteristics, ambitious, tireless in the work but still consider his subordinate abilities. Leaders provide positive energy to subordinates in the form of encouragement, ready to help when there is a job that is not understood by his subordinate.